2022
DOI: 10.31537/laplace.v5i2.762
|View full text |Cite
|
Sign up to set email alerts
|

Kemampuan Pemecahan Masalah Matematis Siswa Sma Melalui Model Pembelajaran Missouri Mathematics Project (Mmp)

Abstract: Model pembelajaran Missouri Mathematics Project (MMP) adalah model pembelajaran yang dirancang agar dapat meningkatkan kemampuan siswa dalam memahami konsep, dan memecahkan masalah yang ada dalam matematika. Keutaman model pembelajaran Missouri Mathematics Project (MMP) ini yaitu dapat meningkatkan keterampilan siswa dalam mengerjakan soal matematika dengan adanya latihan terkontrol, seatwork, dan pekerjaan rumah yang berkaitan dengan kemampuan pemecahan masalah matematis siswa. Penelitian ini bertujuan untuk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
0
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
1
0
0
2
Order By: Relevance
“…Missouri Mathematics Project (MMP) is one of the learning models that can improve students' problem-solving ability (Sadat, 2016). This statement is in accordance with the results of research by Alba (2013), Faroh (2014, Latifah (2014), Ansori (2015), Masriah (2015), Shah (2015), and Faroh (2017) which show that the Missouri Mathematics Project (MMP) model can improve students' mathematical problem-solving ability. In Ansori's (2015) research conducted at SMP N 26 Banjarmasin, it showed that the problem-solving ability of students in the MMP learning model were in the good category for each problem-solving step.…”
Section: Introductionsupporting
confidence: 79%
“…Missouri Mathematics Project (MMP) is one of the learning models that can improve students' problem-solving ability (Sadat, 2016). This statement is in accordance with the results of research by Alba (2013), Faroh (2014, Latifah (2014), Ansori (2015), Masriah (2015), Shah (2015), and Faroh (2017) which show that the Missouri Mathematics Project (MMP) model can improve students' mathematical problem-solving ability. In Ansori's (2015) research conducted at SMP N 26 Banjarmasin, it showed that the problem-solving ability of students in the MMP learning model were in the good category for each problem-solving step.…”
Section: Introductionsupporting
confidence: 79%
“…Pemecahan masalah merupakan proses yang dipakai untuk menyelesaikan masalah (Latifah & Madio, 2014;Azizah & Sundayana, 2016;Pratiwi, Rusdi, & Putri, 2017). Pemecahan masalah menurut Mayer merupakan suatu proses dengan beragam langkah, dimana pemecah masalah harus menemukan hubungan antara pengalaman (skema) masa lalunya dengan masalah yang sekarang dihadapinya dan kemudian bertindak untuk menyelesaikannya (Kirkley, 2003).…”
Section: Pendahuluanunclassified
“…Salah satu aspek yang penting untuk dikembangkan dalam pembelajaran matematika di sekolah adalah kemampuan pemecahan masalah (Latifah & Madio, 2014;Albab, Saputro, & Nursyahidah, 2017;Asih & Ramdhani, 2019;Setiawan, Muhammad, & Soeleman, 2021). Pada panduan standar kompetensi mata pelajaran matematika yang dikeluarkan oleh Depdiknas, disebutkan bahwa kemampuan pemecahan masalah merupakan salah satu dari tujuan diadakannya pembelajaran matematika di sekolah (Depdiknas, 2006: 140).…”
Section: Pendahuluanunclassified